DESKRIPSI JENIS-JENIS IKAN HASIL TANGKAPAN NELAYAN DI PERAIRAN DANAU LIMBOTO - Lamondo, Djuna (Sainstek, 2007)
This study is descriptive research that aimed to find out the fish species which capture by fishermen in Limboto lakes, index of diversity and fish nutrition status. This study using survey method and was done in 6 month, from February to July 2007. Sampling was done in 3 stations, those are, 1st station in Batudaa, 2nd station in Limboto, and 3rd station in Telaga. Sampling based on the type of the capture equipment with 6 replications. The captured fish was identified by determination key, the index of diversity determined using Shannon-wiener diversity index. The fish nutrition index determined using Foultons formula about the coefficient of fish nutrition value. The result showed, there are 12 species fish that captured by fisherman in Limboto lake, those are, Oreochromis niloticus (Ikan Nila), Oreochromis mossambicus (Ikan Mujair), Glossogobius giurus (Ikan Manggabai), Ophiochara sp (Ikan Belosoh), Ophiochara porocephala (payangga), Trichogaste trichopterus (Ikan Sepat), Clarias batrachus (Ikan Lele), Trichogaster pectoralis (Ikan Sepat Siam), Clarias striata (Ikan Gabus), Anabas testudineus (Ikan Betok), Berbodes gonionotus (Ikan Tawes) dan Angguilla marmorata (Ikan Sidat). Index diversity value (H) is 6,48 and the coefficient of fish nutrition (NVC) of Oreochromis niloticus is 1,92, Oreochromos mosambicus is 1,57, Glossogobius giurus is 0,70, Ophiochara sp is 0,91, Ophiochara porocephala is 0,97, Trichagaster trichopterus is 1,42, Clarias batrachus is 1,27, Trichogaster pectroralis 1,37, Channa striata 2,16, Anabas testudineus is 1,55, Barbodes gonionotus is 1,3 and Anguilla marmorata is 1,95